RANCANG BANGUN PROTOTYPE UNMANNED AERIAL VEHICLE (UAV) SEBAGAI PENDUKUNG PENGIRIMAN BARANG DI MASA PANDEMIK COVID-19 - Rian Arta Prahesa, - (2021)
In the conditions of the COVID-19 pandemic, direct delivery of goods has the potential to spread the virus. This is due to direct contact between the courier and the recipient. The use of Autonomous Vehicles can help the delivery process by reducing the risk of spreading the COVID-19 virus. On this basis, an Unmanned Aerial Vehicle (UAV) vehicle was created which could be operated autonomously and was expected to be able to deliver goods by reducing direct contact during the COVID-19 pandemic. This vehicle is made by designing and designing hardware. As well as making GUI programs, QR code scanners, and flight missions that are made using the Python programming language and run on the IDLE Python application. In addition, a monitoring system is also made on the UAV vehicle so that it can be controlled and monitored when carrying out a flight mission. The UAV rides are made of a hexacopter type equipped with an item drop system with dimensions of 10 cm x15 cm x20 cm with a shipping weight limit of 300 grams as a prototype. This UAV vehicle is also equipped with a QR code scanning system to identify the latitude and longitude coordinates of the recipient's address. For the UAV vehicle monitoring system, a GUI (Graphical User Interface) is created which can control and display the conditions of the UAV vehicle in real time. This monitoring system uses a wifi network as a link between the UAV vehicle and the GCS (Ground Control Station). Experiment results state that the GUI created can control and display the conditions of the UAV vehicle. QR code scanner that is created can identify the recipient's destination address. In addition, the UAV vehicle that was made can deliver goods with an average distance difference of 1.28 meters from the point of destination of delivery of goods. Thus this UAV vehicle can be used for the delivery of goods. Keyword : COVID-19, Unmanned Aerial Vehicle, Hexacopter, QR Code Scanner, Graphical User Interface, Ground Control Station.